RETRACTED ARTICLE: Fatal factitious Cushing syndrome (Münchhausen's syndrome) in a patient with macroprolactinoma and silent corticotrophinoma: case report and literature review. Issue 1 (December 2015) - Minanni, Carlos; Almeida Cardoso, Ana; Albuquerque Albuquerque, Edoarda; Brito, Luciana; Lopes, Ludmilla; Glezer, Andrea; Verduguez, Elisa; Mendonça, Berenice; Bronstein, Marcello; Machado, Marcio; Fragoso, Maria
Abstract Münchhausen's syndrome (MS) is a chronic factitious disorder characterized by the intentional production of clinical symptoms without external incentive. One type of MS is factitious Cushing syndrome, an extremely rare clinical situation in which the diagnosis is challenging mainly due to interference of the exogenous medication in cortisol immunoassays. We described a 26-year-old woman who was originally diagnosed with a macroprolactinoma and during follow-up developed clinical and laboratorial hypercortisolism. A transsphenoidal surgery was performed and immunohistochemistry revealed positive and diffuse staining for both hormones. Four years later, her hypercortisolism recurred and the confirmation of factitious Cushing syndrome was delayed due to conflicting laboratorial results. There are few cases in the literature of factitious Cushing syndrome, and only one had a fatal outcome. The diagnosis of this condition is complex and includes cyclic Cushing syndrome in the differential diagnosis. These patients have high morbidity and increased mortality risk and are likely to have other psychiatric disorders. Prednisone was identified as the culprit in the majority of the cases.